2014
DOI: 10.1371/journal.pone.0091203
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hippocampal Excitability in the 3xTgAD Mouse Model for Alzheimer's Disease In Vivo

Abstract: Mouse Alzheimer's disease (AD) models develop age- and region-specific pathology throughout the hippocampal formation. One recently established pathological correlate is an increase in hippocampal excitability in vivo. Hippocampal pathology also produces episodic memory decline in human AD and we have shown a similar episodic deficit in 3xTg AD model mice aged 3–6 months. Here, we tested whether hippocampal synaptic dysfunction accompanies this cognitive deficit by probing dorsal CA1 and DG synaptic responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 62 publications
9
51
1
Order By: Relevance
“…Moreover, our findings support recent studies in humans and rodent models linking hippocampal overactivity and hyperexcitability to age-related memory deficits (Koh et al 2010;Bakker et al 2012;Davis et al 2014) and are consistent with the correlation of hippocampal overactivity with memory deficits in schizophrenia (Tregellas et al 2014). However, hippocampal neural disinhibition may facilitate hippocampal synaptic plasticity and, thereby, improve memory, if such disinhibition is finely and dynamically regulated by endogenous plasticity (Donato et al 2013) or if there is a pre-existing deficit due to increased neural inhibition (Fernandez et al 2007).…”
Section: Memory Deficitssupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, our findings support recent studies in humans and rodent models linking hippocampal overactivity and hyperexcitability to age-related memory deficits (Koh et al 2010;Bakker et al 2012;Davis et al 2014) and are consistent with the correlation of hippocampal overactivity with memory deficits in schizophrenia (Tregellas et al 2014). However, hippocampal neural disinhibition may facilitate hippocampal synaptic plasticity and, thereby, improve memory, if such disinhibition is finely and dynamically regulated by endogenous plasticity (Donato et al 2013) or if there is a pre-existing deficit due to increased neural inhibition (Fernandez et al 2007).…”
Section: Memory Deficitssupporting
confidence: 89%
“…It is entirely consistent with these studies that hippocampal neural disinhibition, which increases hippocampal burst firing and, by way of hippocampo-prefrontal functional connectivity, would modulate prefrontal function, causes similar selective reductions in accuracy on the 5CSRT task. Interestingly, both the pilocarpine rat model (Kumar and Buckmaster 2006) and the triple transgenic mouse model of Alzheimer's disease (Davis et al 2014) show hippocampal hyperexcitability; our new finding that hippocampal neural disinhibition causes attentional impairments suggests that hippocampal hyperexcitability may contribute to the attentional deficits in these rodent models. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 …”
Section: Attentional Deficitsmentioning
confidence: 88%
“…Hyperexcitability has been described in AD models and patients and can be the trigger for glutamatergic overstimulation (Davis et al, 2014;Friedman et al, 2012;Noebels, 2011;Palop and Mucke, 2009). Pyruvate, in association with 3-beta-hydroxybutyrate, has been shown to reduce epileptiform activity in a AD mouse model (Zilberter et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Given the enhanced neuronal excitability observed in 3xTg-AD mice in vivo (Davis et al, 2014), we explored whether the phenomenon could be attenuated by pyruvate. To gather information of pyruvate effects on the excitability of our Tg AD cultures, spontaneous activity was investigated in 3xTg-AD cultured neurons by measuring Ca 2+ spikes.…”
Section: Chronic Pyruvate Treatment Decreases Spontaneous Ca 2+ Spikementioning
confidence: 99%
“…In vitro and animal model studies have demonstrated that Aβ pathology associates with increased excitability of hippocampal neurons, leading to hypersynchronous network activity and higher risk for seizures (Born et al, 2014; Brown et al, 2011; Busche et al, 2012; Davis et al, 2014; Del Vecchio et al, 2004; Minkeviciene et al, 2009; Palop et al, 2007; Putcha et al, 2011). Epidemiologic studies have confirmed comorbidity between patients with AD and epilepsy, showing increased risk of seizures in AD patients (Amatniek et al, 2006; Hommet et al, 2008).…”
Section: Introductionmentioning
confidence: 99%